From Ancient Rome to Brasília: the planned city was not made for the poor residentes: De Roma antiga à Brasília: a cidade planejada não foi feita para os pobres (Revista de História da UEG (REVHIST), 2023)
Based on a dialogue with several city and urbanization researchers, this study draws a comparation between the importante old urban centers and some of the current Brazilian metropolises, showing a commom permanence between them, the segregation of their poor residents. In other words, the text addresses how throughout the growth of cities, urban planning promoted the spatial exclusion of the less affluent population, keeping it away, peripheral and unassisted. Keywords: Urban Planning. Housing. Spatial Segregation.